A multi-centre randomised clinical trial of oral hygiene interventions following strokeA 6-month trial - Ab Malik, N; Yatim, SM; Razak, FA; Lam, OLT; Jin, L; Li, LSW; McGrath, C (Wiley, 2024)
Indexed by WOS/SCOPUS/ERA